Complexes of star-shaped cationic polyelectrolytes with anionic liposomes: Towards multi-liposomal assemblies with controllable stability. (14th June 2016) - Sybachin, Andrey V.; Zaborova, Olga V.; Pergushov, Dmitry V.; Zezin, Alexander B.; Plamper, Felix A.; Müller, Axel H.E.; Kesselman, Ellina; Schmidt, Judith; Talmon, Yeshayahu; Menger, Fredric M.; Yaroslavov, Alexander A.
Abstract: Complexes were formed via the electrostatic interaction between 30–50 nm anionic liposomes and a star-shaped polyelectrolyte, poly[2-(methacryloyloxy)ethyl]trimethyl ammonium iodide, having cationic arms that radiate from a silicon-based central core. The complexation was investigated with attention given to assessing the capacity of the cationic stars for the anionic liposomes (both liquid and solid); the integrity of the complexed liposomes; and the stability of the resulting star/liposome complexes in aqueous salt solutions. We have found that by changing the content of anionic groups in the liposomal membrane as well as the phase-state of membrane, the stability of star/liposome complexes in aqueous salt media can be controlled. The liquid liposomes with 0.1 mol fraction of anionic palmitoyloleoylphosphatidylserine (POPS 1− ), and solid liposomes with 0.1 mol fraction of POPS 1−, retain their integrity when bound to the stars, with the resulting star/liposome complexes being stable in physiological solution, i.e. [NaCl] = 0.15 M. Multi-liposomal complexes containing up to 12 liposomes per star seem to hold promise as carriers for biologically active compounds. Graphical abstract: Highlights: Multiliposomal complexes of the liposomes of various composition assembled on polycationic stars are described. The requirements for the star/liposomes complexes with intact vesicles, remaining stable in physiological solution, are formulated. Liposome/star complexes are visualized by using cryo-TEM.